COMPUTER VISION SYNDROME AND NECK RANGE OF MOTION IN OFFICE EMPLOYEES - Setiawan, Christin; Ernawati, Titiek; Nugroho, Nunung (JOURNAL OF WIDYA MEDIKA JUNIOR, 2021)
Introduction: A lot of employees working in front of a computer complaining about somesymptoms. Eye and vision problems connected to the prolonged use of a computer are calledComputer Vision Syndrome (CVS) or Digital Eye Strain. One of the symptoms of CVS isneck pain. In comparison, Range of Motion (ROM) is used to determine the ability of jointmovements. Aside from that, it can also be used to maintain flexibility and joint mobility.Purpose: To explain the association between Computer Vision Syndrome and the reductionin neck range of Motion in Employees.Method: The type of this research is analytic observational, and the design of this research isCross-Sectional Study. This research was conducted from Tuesday, 16th July 2019, untilWednesday, 17th July 2019, using CVS-Q and goniometer dy.Results: We collected 156 respondents that meet the inclusion and exclusion criteria. Weobtain p=0,02, p <0,05 meaning there is an association between Computer Vision Syndromeand the neck range’s Motion.Conclusion: To conclude, there is an association between Computer Vision Syndrome andthe neck range’s Motion.